2017
DOI: 10.4111/icu.2017.58.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal fibrosis-clinical presentation and outcome analysis from urological perspective

Abstract: PurposeTo study clinical presentation, laboratory results, imaging findings and treatment options and outcomes of retroperitoneal fibrosis (RPF). To determine whether it follows the same natural course and response to treatment in the Asian population as in the Western world.Materials and MethodsMedical records of patients diagnosed with RPF on imaging and histopathology between February 2010 and April 2016 were reviewed.ResultsOf the 21 patients analyzed, mean age at presentation was 50.81 years. The male to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, this is the first report on the occurrence of renal fungal ball in a patient with RPF. This disease is characterised by chronic inflammation of the retroperitoneum, which leads to entrapment and obstruction of the peritoneal structures including the ureters . Consistent with the Review published studies, our patient also had ureteric obstruction which predisposed him to have renal fungus ball.…”
Section: Discussionsupporting
confidence: 88%
“…To the best of our knowledge, this is the first report on the occurrence of renal fungal ball in a patient with RPF. This disease is characterised by chronic inflammation of the retroperitoneum, which leads to entrapment and obstruction of the peritoneal structures including the ureters . Consistent with the Review published studies, our patient also had ureteric obstruction which predisposed him to have renal fungus ball.…”
Section: Discussionsupporting
confidence: 88%
“…16 In patients with aortitis or retroperitoneal fibrosis the ureter diverts medially and therefore forms more fistulas with the aorta. 17…”
Section: Discussionmentioning
confidence: 99%
“…There were some similar typical cases published currently [14][15][16]; more details are provided in Table 1. Previous studies reported that abnormal laboratory findings included normochromic normocytic anemia, elevated inflammatory markers, abnormal renal function and positive autoimmune tests [10,17]. Some cases were accompanied by elevated serum IgG4 [9,18,19].…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, less common complications include lower-extremity edema with possible deep venous thrombosis, constipation, scrotal swelling, varicocele and hydrocoele. When symptoms of renal failure appear, there is a high probability of ureteral obstruction [10,11]. These symptoms are nonspecific and thus may not be helpful in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%